Research on Campus Network Equipment Environment Monitoring Based on Internet of Things - Liu, Jianwei (Informatica, 2021)
The working environment of equipment has a great impact on the performance of equipment; therefore, it needs to be monitored and managed effectively. Based on the Internet of things (IoT), this study analyzed the monitoring of the campus network equipment environment. A monitoring system was designed, the design methods of software and hardware were analyzed, and the system was tested. The test results showed that the sensor used in the system had high accuracy, the temperature error was ± 0.5 ℃, the humidity error was within 0.5% RH, the data transmission performance was good, the transmission delay was between 8 ms and 9 ms, and the average packet loss rate was 0.7%. The test results verify the effectiveness of the designed system, and the system can be popularized and applied in the actual campus network.